REVERSIBLE OCULAR ADVERSE EFFECTS IN MELANOMA TREATMENT WITH MEK/BRAF INHIBITORS - Vasović, Dolika; Rašić, Dejan M.; Marjanović, Ivan; Kalezić, Tanja; Lučić, Margita (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: MEK/BRAF inhibitors, including cobimetinib and vemurafenib, are effective in managing BRAF-mutant melanoma. Despite their efficacy, these therapies may cause adverse effects, including ocular toxicities. Although uncommon, these complications can significantly impact a patient’s quality of life and adherence to treatment. This case report highlights a 57-year-old female who developed ocular side effects during MEK/BRAF inhibitor therapy, underscoring the need for early recognition and management. Case report: A 57-year-old female received MEK/BRAF inhibitors (cobimetinib and vemurafenib) for eight months after surgery for skin melanoma. During treatment, she developed significant ocular adverse effects, including bilateral pigmented keratic precipitates, anterior chamber inflammation, and vitritis, resulting in reduced visual acuity. Ophthalmologic examination revealed signs of inflammation, prompting a three-week suspension of the therapy. After discontinuing the treatment, the patient experienced marked improvement, with her visual acuity returning to 20/20. Subsequent examinations confirmed the resolution of ocular symptoms, indicating that the adverse effects were linked to the therapy rather than metastatic disease. Conclusion: This case highlights the importance of identifying and managing ocular toxicities associated with MEK/BRAF inhibitors. Although rare, these complications can severely affect quality of life and treatment continuation. A multidisciplinary approach, involving both oncologists and ophthalmologists, is essential for monitoring and addressing these issues. Further research is needed to better understand the mechanisms behind these adverse effects and to improve management strategies for patients on targeted melanoma therapy.